2021
DOI: 10.1136/bmj.n2342
|View full text |Cite
|
Sign up to set email alerts
|

Role of asymptomatic and pre-symptomatic infections in covid-19 pandemic

Abstract: Liming Li and colleagues highlight the importance of identifying people without symptoms to control outbreaks of covid-19Box 1: Definitions of asymptomatic and pre-symptomatic Asymptomatic infectionAn asymptomatic case is one in which someone has laboratory confirmed SARS-CoV-2 infection but does not develop symptoms (ie, fever, dry cough, fatigue). Asymptomatic transmission refers to transmission of the virus from a person who did not develop disease symptoms. Pre-symptomatic infectionPre-symptomatic cases ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…These were people who, due to persistent symptoms after contracting COVID-19, were seeking further diagnosis and treatment. According to this review results, over 99% of patients presented clinical symptoms, which obviously contradicts current medical evidence, which indicates that COVID-19 may be asymptomatic in even 8–30% of cases [ 41 ]. Due to the above, the results of this study should not be analyzed in relation to the entire population.…”
Section: Discussionmentioning
confidence: 95%
“…These were people who, due to persistent symptoms after contracting COVID-19, were seeking further diagnosis and treatment. According to this review results, over 99% of patients presented clinical symptoms, which obviously contradicts current medical evidence, which indicates that COVID-19 may be asymptomatic in even 8–30% of cases [ 41 ]. Due to the above, the results of this study should not be analyzed in relation to the entire population.…”
Section: Discussionmentioning
confidence: 95%
“…Since a transmission event is associated with a location linked to communities on the road network, over time, public health can use the PPT to predict/estimate the risk for the communities liked to the road network. Notably, we estimate that asymptomatic and presymptomatic cases will account for 15% and 52% of the notified positive cases, respectively, 25 which are associated with a lower secondary transmission risk. Such estimates will be contextualised using our empirical data and used to evaluate the tool’s effectiveness for contact tracing, that is, the sensitivity and proportion of expected false positive contact notification.…”
Section: Methodsmentioning
confidence: 92%
“…Then it is reasonable to assume that r I = 1/13.4 per day and r A = 1/8 per day. Gao et al (2021) discovered that 76% of seropositive infections were accompanied by no symptoms based on a study among 34857 participants in China. In addition, they found that the relative transmissibility varied from 0.35 to 0.58 for asymptomatic cases and was 0.63 for pre-symptomatic cases.…”
Section: Parameter Estimationmentioning
confidence: 99%
“…info/coronavirus/country/us/). We assume that A[1] = 0.76I [1]/0.24 according to Gao et al (2021). It follows that…”
Section: Parameter Estimationmentioning
confidence: 99%